Lucky chance cowboy - Stanley, Teri Anne (Big chance dog rescue, 2020)
"Marcus Talbott is a soldier through and through, and he's not going to let an injury keep him from his Army unit. Sure, his last mission nearly broke his back, but that's nothing his positive attitude and work ethic can't fix, right? In the meantime, he's got a place on the board at the Big Chance Dog Rescue, and flirting with his friend's sassy sister, Emma, is a welcome distraction. Emma Stern is barely scraping by while working and caring for her elderly grandfather, but she's running out of options--and hope. The last thing she has time for is Marcus and his flirting, sexy as he might be. But every time Emma thinks she's reached the end of her rope, Marcus is there to lend a hand. Maybe there's more to the handsome playboy after all..." --